The adman's dilemma : Barnum to Trump - Rutherford, Paul, 1944- (University of Toronto Press, 2018)
"The Adman's Dilemma is a cultural biography that explores the rise and fall of the advertising man as a figure who became effectively a licensed deceiver in the process of governing the lives of American consumers. Apparently this personage was caught up in a contradiction, both compelled to deceive yet supposed to tell the truth. It was this moral condition and its consequences that made the adman so interesting to critics, novelists, and eventually filmmakers. The biography tracks his saga from its origins in the exaggerated doings of P.T. Barnum, the emergence of a new profession in the 1920s, the heyday of the adman's influence during the post-WW2 era, the later rebranding of the adman as artist, until the apparent demise of the figure, symbolized by the triumph of that consummate huckster, Donald Trump. In The Adman's Dilemma, author Paul Rutherford explores how people inside and outside the advertising industry have understood the conflict between artifice and authenticity. The book employs a range of fictional and nonfictional sources, including memoirs, novels, movies, TV shows, websites, and museum exhibits to suggest how the adman embodied some of the strange realities of modernity."--